Surface osteosarcoma: Predictors of outcomes. Issue 4 (27th May 2021) - Lee, Stella J.; Lans, Jonathan; Cook, Samuel D.; Chebib, Ivan; Schwab, Joseph H.; Raskin, Kevin A.; Lozano‐Calderón, Santiago
Abstract: Background and Objectives: The subtypes of surface osteosarcomas include well‐differentiated, low‐grade parosteal osteosarcoma (POS), intermediate‐grade periosteal osteosarcoma (PerOS), high‐grade surface osteosarcoma (HGSO), and high‐grade, dedifferentiated POS (dPOS). We aimed to determine disease progression, defined as local recurrence and metastatic disease, and overall (OS) and disease‐specific survival (DSS). We identify outcome predictive factors and report functional results. Methods: This retrospective study evaluated patients with primary surface osteosarcoma at our hospital from 1992 to 2019. Fifty‐one patients had a median follow‐up of 6.1 years (range: 0.1–25.2). Histologic subtypes included 32 POS, 11 PerOS, 4 HGSO, and 3 dPOS. Bone and soft tissue margins were classified using the American Joint Committee on Cancer residual tumor classification (Rx = Not evaluable; R0 = negative margin; R1 = microscopic positive margin; and R2 = macroscopic positive margin) and the modified R classification (mRx = not evaluable; mR0 = negative margin >1 mm; mR1 = negative margin ≤1 mm; mR1‐dir: Positive microscopic margin locally; mR2a: Positive macroscopic margin locally; mR2b: positive macroscopic margin distally; and mR2C: positive macroscopic margin locally and distally). Forty‐one patients had functional outcomes. Results: Three POS patients developed recurrence: two had R0 margins and one an intralesional resection. Five patients developed lung metastases (POS: 3, dPOS: 2). Four patients died. The only significant disease progression predictor was age. OS at 10 years was 97%. 48 patients had negative bone margins (R0 or mR0 and mR1) and 47 patients had negative soft‐tissue margins (R0 or mR0 and mR1). The average MSTS score was 88.43 (range: 34.29–100). Conclusions: We advocate surgery for POS and believe R0 (mR0 and mR1 resections) or planned R1 (mR1‐dir) to preserve function are acceptable. We favor chemotherapy and surgery for PerOS, though a chemotherapeutic response is highly variable. High‐grade tumors are the most infrequent subtype, but HGSO and dPOS seem to portend a poorer prognosis. Good function can be obtained.